Platelet aggregation impacts thrombin generation assessed by calibrated automated thrombography - Mélusine Didelot; Clémence Docq; Denis Wahl; Patrick Lacolley; Véronique Regnault; Jérémy Lagrange (Platelets, 2018)
A calibrated automated thrombogram (CAT) is performed usually with human platelet-free plasma (PFP) but may be more relevant with platelet-rich plasma (PRP). In this case, platelets are not stimulated by subendothelial molecules like collagen. Our aim was to assess the consequence of strong (collagen) or weak (ADP) induction of platelet release and aggregation on thrombin generation. Platelet aggregation in PRP was triggered with 10 µg/mL collagen or 10 µM ADP using a lumi-aggregometer. Thrombin generation curves were monitored by CAT in different conditions: PRP, PRP with activated platelets (actPRP), aggregated PRP (agPRP), aggregated platelets resuspended in autologous PFP (resPRP), PFP and PFP obtained after aggregation (agPFP). We found a 3-fold shortening of the lag time and time to peak and a marked increase in velocity and thrombin peak without changes in endogenous thrombin potential (ETP) in agPRP with both agonists compared with PRP. The same holds true in agPFP but with a marked increase in ETP compared with PFP. Similar changes in the kinetics of thrombin generation were observed with actPRP-collagen and to a lesser extent in resPRP-collagen compared with PRP. By contrast, there were no modifications of the thrombin generation curves in actPRP-ADP. Alpha-2-macroglobin-thrombin complexes were unchanged in the different PRP conditions but were increased in PFP prepared from agPFP compared to control PFP. Platelet aggregation during activation by agonists other than thrombin did not increase thrombin generation but accelerated its kinetics mainly via platelet content release and platelet-derived extracellular vesicules formation. In diseases characterized by altered platelet granule content or release as well as altered platelet activation, a platelet aggregation step prior to CAT analysis may be clinically relevant to improve laboratory estimation of the bleeding/thrombotic balance.